The GRHL2/ZEB Feedback Loop—A Key Axis in the Regulation of EMT in Breast Cancer. Issue 9 (3rd May 2017) - Mooney, Steven M.; Talebian, Vida; Jolly, Mohit Kumar; Jia, Dongya; Gromala, Monica; Levine, Herbert; McConkey, Brendan J.
ABSTRACT: More than 90% of cancer‐related deaths are caused by metastasis. Epithelial‐to‐Mesenchymal Transition (EMT) causes tumor cell dissemination while the reverse process, Mesenchymal‐to‐Epithelial Transition (MET) allows cancer cells to grow and establish a potentially deadly metastatic lesion. Recent evidence indicates that in addition to E and M, cells can adopt a stable hybrid Epithelial/Mesenchymal (E/M) state where they can move collectively leading to clusters of Circulating Tumor Cells—the "bad actors" of metastasis. EMT is postulated to occur in all four major histological breast cancer subtypes. Here, we identify a set of genes strongly correlated with CDH1 in 877 cancer cell lines, and differentially expressed genes in cell lines overexpressing ZEB1, SNAIL, and TWIST. GRHL2 and ESRP1 appear in both these sets and also correlate with CDH1 at the protein level in 40 breast cancer specimens. Next, we find that GRHL2 and CD24 expression coincide with an epithelial character in human mammary epithelial cells. Further, we show that high GRHL2 expression is highly correlated with worse relapse‐free survival in all four subtypes of breast cancer. Finally, we integrate CD24, GRHL2, and ESRP1 into a mathematical model of EMT regulation to validate the role of these players in EMT. Our data analysis and modeling results highlight the relationships among multiple crucial EMT/MET drivers including ZEB1, GRHL2, CD24, and ESRP1, particularly in basal‐like breast cancers, which are most similar to triple‐negative breast cancer (TNBC) and are considered the most dangerous subtype. J. Cell. Biochem. 118: 2559–2570, 2017. © 2017 Wiley Periodicals, Inc. Abstract : In this work, we delineate the genes responsible for epithelial to mesenchymal transition in breast cancer. Work is confirmed in human tissue of patients with various cancer subtypes.